Membangun Kedekatan Sosial Dan Keagamaan Melalui Kegiatan Pengabdian Mahasiswa Kkn Di Jorong Limau Puruik - Nuzul Hidayat; Mutia Retno Sari; Khairunnida Khairunnida; Rahmania Shafa Khalila; M. Risky Akbar Handani; Afira Putra Muhammad Rafi’i; Andiny Ersyahril Syaputri; Habibi Febriandika (CV. ITTC INDONESIA, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of community engagement aimed at implementing the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi) through the direct involvement of university students in addressing various social and religious issues within the community. This article aims to describe the implementation and impact of KKN student service activities in fostering social and religious cohesion among the people of Jorong Limau Puruik. The method employed was a participatory approach that actively involved community members in every stage of the program, including observation, planning, implementation, and evaluation. The activities carried out included the installation of name boards for three prayer houses (musala), namely Musala Nurul Hakim, Musala Nurul Ikhlas, and Musala Nurul Ikhsan, as well as the organization of religious competitions such as the Qur’anic Recitation Competition (Musabaqah Tilawatil Qur’an/MTQ), Qur’anic Speech Competition (Musabaqah Syarhil Qur’an/MSQ), and Islamic Quiz Competition. The results indicated that the installation of the prayer house name boards successfully enhanced the identity and visibility of religious facilities while increasing community awareness and concern for places of worship. Meanwhile, the religious competitions encouraged greater participation among children and adolescents in religious activities, broadened their Islamic knowledge, and fostered religious character development. In addition to strengthening religious values, these activities also enhanced social relationships through cooperation, mutual assistance, and active community participation throughout the program. Therefore, social and religious-based KKN programs have proven effective in strengthening social solidarity, improving the quality of religious life, and fostering harmonious relationships between university students and the community in Jorong Limau Puruik.